2012
DOI: 10.1186/1756-9966-31-65
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated EGFR expression may predict outcome of EGFR-TKIs therapy for the advanced NSCLC patients with wild-type EGFR

Abstract: BackgroundEGFR mutation is a strong predictive factor of EGFR-TKIs therapy. However, at least 10% of patients with EGFR wild-type are responsive to TKIs, suggesting that other determinants of outcome besides EGFR mutation might exist. We hypothesized that activation of phosphorylated EGFR could be a potential predictive biomarker to EGFR-TKIs treatment among patients in wild-type EGFR.MethodTotal of 205 stage IIIb and IV NSCLC patients, tissue samples of whom were available for molecular analysis, were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 39 publications
1
39
0
1
Order By: Relevance
“…Furthermore, the up-regulation of pY1173 also has been reported in patients who have NSCLC with EGFR mutation, and Akt, MAPK, and Stat3 signaling is higher in pY1173-positive patients (43). It also has been shown that patients with stage IIIb and IV NSCLC with positive pY1173 staining have a shorter superior progression-free survival rate than patients with negative pY1173 staining (44). These data suggest that site-specific phosphorylation of EGFR plays an important role in the maintenance of TKI resistance and that targeting these selective EGFR phosphorylations could be a future direction for drug discovery.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the up-regulation of pY1173 also has been reported in patients who have NSCLC with EGFR mutation, and Akt, MAPK, and Stat3 signaling is higher in pY1173-positive patients (43). It also has been shown that patients with stage IIIb and IV NSCLC with positive pY1173 staining have a shorter superior progression-free survival rate than patients with negative pY1173 staining (44). These data suggest that site-specific phosphorylation of EGFR plays an important role in the maintenance of TKI resistance and that targeting these selective EGFR phosphorylations could be a future direction for drug discovery.…”
Section: Discussionmentioning
confidence: 86%
“…EGFR is a 170 kDa tyrosine kinase receptor consisting of an extracellular ligand-binding domain, a transmembrane lipophilic domain, and an intracellular tyrosine kinase domain and the C-terminus region with multiple tyrosine residues [26]. EGFR mediates signals that stimulate proliferation, migration, and metastasis in many tumour types [25,27], and its signal transduction is regulated by stimulatory and inhibitory inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its effectiveness, a considerable fraction of patients do not respond to the treatment. EGFR pY1068 has emerged as a predictive biomarker for screening patients with wild-type EGFR that will respond to Gefitinib [128]. Imatinib (Gleevec) is another anti-cancer drug targeting the constitutively active BCR-Abl tyrosine kinase that results in chronic myeloid leukaemia (CML).…”
Section: Targeted Phosphoproteomics: Potential Clinical Applicationsmentioning
confidence: 99%